PROFILING GRADE STUDENTS’ SCIENCE PROCESS SKILLS IN LEARNING INHERITANCE OF TRAITS - Nikmah Alfiatun; Endah Rita Sulistya Dewi; M. Syaipul Hayat (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2026)
This study aims to investigate and comprehensively describe the profile of Science Process Skills (SPS) among grade XII students in the biology material on Inheritance of Traits at SMA Negeri 1 Ngawen. The study uses a quantitative approach, employing the Research and Development (R&D) method and adapting the ADDIE development model. Quantitative data collection was carried out through tests using SPS assessment instruments in the form of structured essay questions that include 6 main indicators: observing, classifying, predicting, measuring and using numbers, concluding, and communicating. The results of data analysis show a very uneven distribution of students' SPS abilities: only 1.47% of students are included in the